The Characteristics of Effective Professional Development That Affect Teacher’s Self-Efficacy and Teaching Practice - Bachtiar Bachtiar (EDUVELOP, 2020)
Many research suggests that effective professional development (PD) can help teachers increase their knowledge, skills and understanding about teaching. Research evidence also indicates that good quality PD enhances teacher sense of efficacy. This study aims to investigate the characteristics of good quality PD that affect teachers’ self-efficacy from the perspective of junior secondary English Language teachers in Indonesia. Data derived from the initial and follow-up questionnaires, TSG observations, and semi-structured interviews. The findings found that English language teachers perceived good quality PD are those activities that increase teachers’ knowledge and teaching skills, encourages collaboration, and is based on teachers’ classroom practical needs. The study suggests the need to involve teachers in the process of planning, designing, and implementing PD in order to maximize its benefits.